Expert review and pretesting of behavioral supervision in higher education - Habsah, Muda; Natasha Shazleen, Badrul; Zainudin, Awang (2020)
Purpose: The rationale for the postgraduate supervision measures for higher education by the call for universities to adopt a systematic practice in postgraduate supervision through new supervisors' exposure to creative ways of monitoring. This paper aims at understanding, improving and validating the content of behavioral supervision measures using the expert review and pretesting analysis. Design/methodology/approach: The authors developed, modified and operationalized the items based on the developmental supervision theoretical concept by Glickman () to measure the behavioral supervision of postgraduate in higher education. The authors obtain comments and verification from experts for content validity and criterion validity. Later, the authors do pretesting of face validity. Findings: The result of the expert review and pretesting, analysis, provides measures (items) for the following seven stages (components) of postgraduate behavioral supervision: listening/clarifying; encouraging; presenting/demonstrating; negotiating/problem-solving; directing; standardizing and reinforcing. Practical implications: The findings contribute to the rational development of supervision measures and functional transformation in the postgraduate supervision process in higher education at national and international contexts. Social implications: These supervision measures, if practiced by the supervisors and postgraduates' students, will accelerate and achieve the aspiration initiative of the Ministry of Higher Education. In general, based on the needs identified, the positive impact of this study can improve national and international postgraduate program educational outcomes. Originality/value: There is limited number of empirical research which resulted in postgraduate behavioral supervision measures in the context of higher education.